Comparison of Different Methods of Education on Reducing the Anxiety of Patients with Myocardial Infarction - Yeganeh khah MR; Abedini A; Akbari H; Ziyayi Nezhad MT (Iran University of Medical Sciences, 2012)
Background and Aim: Anxiety is one of the most common and most important psychological reactions in patients with acute myocardial infarction which has a very negative effect on the prognosis of their disease and their physical and mental recovery period . Accordingly this study was conducted in order to compare the effects of different education methods on reducing the State-anxiety of patients with myocardial infarction.   Material & Methods: It was an experimental study. Sixty six patients with myocardial infarction hospitalized in a CCU in a hospital in Qom city were recruited by convenience sampling considering the inclusion criteria and were randomly assigned to three equal groups of face-to-face, pamphlet and CD-ROM training methods. Data were collected by Spielberg State-anxiety inventory. State anxiety was measured and compared in three groups before and after intervention. Data were analyzed by SPSS-PC (v.11.5).   Results: The findings showed that the different training methods had significant effects on reducing the state anxiety levels of the sample (P=0/000). However no significant difference was seen between the three experimental groups (P>0/05). Conclusion: Findings suggest that different methods of reducing anxiety in patients with acute myocardial infarction are effective . So using all three methods is advisable .